Insights from the maternal lineage of the F2 generation after exposure to an environmentally relevant dose of benzo(a)pyrene in the male rats of F0 generation - Jorge, Bárbara Campos [UNESP] (2023)
Benzo(a)pyrene (BaP) is a substance with the potential to induce endocrine disruption in the F0 generation and cause adverse multigenerational effects (F1 generation) for reproductive parameters in rats. The objective of this study was to investigate the occurrence of transgenerational inheritance in the reproductive aspects of male and female rats belonging to the F2 generation (MF2). This investigation was conducted following the exposure of male rats from the F0 generation to BaP to assess potential effects on subsequent generation from the maternal lineage (F1). For that, juvenile male Wistar rats (F0) were orally exposed to BaP (0.1 µg/kg/day) for 31 consecutive days. In adulthood, they were mated with untreated females to obtain female offspring (F1), which later produced the MF2. In the MF2 generation, both males and females exhibited increased body weight on postnatal day (PND) 1. In MF2 males, we observed delayed preputial separation, altered pup weight, reduced levels of follicle-stimulating hormone (FSH), increased intratesticular testosterone levels, decreased type A sperm, epididymal disturbances, reduced 5 α-reductase activity, increased testicular proliferation, and alterations in testicular antioxidant enzymes. In MF2 females, we noted morphological uterine enlargement, reduced sexual activity, and decreased progesterone levels. The findings suggest that the alterations observed in both MF2 males and females can be attributed to modifications in the sperm from F0 generation, which were subsequently transmitted to F1 females and MF2 generation due to BaP exposure.